2004
DOI: 10.1128/jcm.42.12.5739-5744.2004
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Detection of Staphylococcus aureus and Coagulase-Negative Staphylococci in Positive Blood Cultures by Real-Time PCR with Two Fluorescence Resonance Energy Transfer Probe Sets

Abstract: A real-time PCR assay that uses two fluorescence resonance energy transfer probe sets and targets the tuf gene of staphylococci is described here. One probe set detects the Staphylococcus genus, whereas the other probe set is specific for Staphylococcus aureus. One hundred thirty-eight cultured isolates, which contained 41 isolates of staphylococci representing at least nine species, and 100 positive blood cultures that contained gram-positive cocci in clusters were tested. This assay was 100% sensitive and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 38 publications
1
40
0
1
Order By: Relevance
“…Multiple studies have reported rapid and accurate detection of S. aureus in blood culture bottles growing GPCC, which speak to the feasibility and interest in this approach (1-3, 5, 6, 9, 10). Accurate detection of the presence of all staphylococci in blood culture bottles and simultaneous identification of S. aureus among them using realtime PCR have also been demonstrated (8). This approach identifies CoNS by actually detecting its presence rather than by assuming its presence in the absence of S. aureus in cultures growing GPCC.…”
mentioning
confidence: 99%
“…Multiple studies have reported rapid and accurate detection of S. aureus in blood culture bottles growing GPCC, which speak to the feasibility and interest in this approach (1-3, 5, 6, 9, 10). Accurate detection of the presence of all staphylococci in blood culture bottles and simultaneous identification of S. aureus among them using realtime PCR have also been demonstrated (8). This approach identifies CoNS by actually detecting its presence rather than by assuming its presence in the absence of S. aureus in cultures growing GPCC.…”
mentioning
confidence: 99%
“…[20][21][22] Conventional PCR, and more recently real-time PCR, have been recognized as efficient tools for clinically applicable assays. 11,12,[23][24][25] The use of these tools is of particular interest in orthopedics, wherein the adhesion of bacteria within a biofilm on the surface of an implant may make the organism difficult to detect by conventional techniques. [15][16][17] Although some of these tools have been used to study orthopedic infections, much remains to be learned.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Clinical microbiologists are more and more commonly using the polymerase chain reaction (PCR) and other nucleic acid amplification assays for the detection and identification of microbial pathogens and to determine the most important mechanisms of antimicrobial resistance. Realtime or homogeneous PCR is a relatively new modification of the PCR, 11,12 wherein amplification and detection occur in the same reaction vessel secondary to the use of fluorescent detector molecules. In the clinical laboratory, this translates into easier to perform assays that are more rapid, features that increase the possible clinical applications of PCR assay.…”
Section: Introductionmentioning
confidence: 99%
“…The tuf gene encodes the elongation factor Tu, which is an essential constituent of the bacterial genome [26]. S. aureus strains produce an extracellular thermostable nuclease (TNase) with a frequency similar to that at which they produce coagulase.…”
Section: Tuf $Enementioning
confidence: 99%